Floral biology and seed technological aspects of jatropha curcas Linn. - Puttaswamy H (Department of Forest Management and Utilisation, College of Forestry, 2008)
The present study entitled “Floral biology and seed technological aspects of Jatropha curcas Linn.” was carried out in College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period of 2006-2007. The plant displayed phenological cycle twice a year for all periodical events viz., leaf shedding, leaf flushing, flowering and fruiting. However, the duration of each stage was high in second season as it coincided with rainy season. Fruiting appeared from 4th week of May to 1st week of July in first season and from 2nd week of October to 3rd week of November in second season. The inflorescence is monoecious with protandry and is racemose with dichasial cyme pattern. The average number of male flowers and female flowers per inflorescence were 136.4 ± 10.82 and 8 ± 0.71 respectively. The inflorescence is having two tiers viz., large tier and small tier. The average length and spread were recorded as 7.624 ± 0.84 cm and 6.373 ± 0.55 cm in large tier, and 6.101 ± 0.99 cm and 4.357 ± 0.36 cm in small tier respectively. In an average, inflorescence has taken 18.9 ± 0.67 days for its development from visual stage of initiation and the time taken for the full bloom of inflorescence was 14.2 ± 0.75 days. The male flower is greenish white, odourless and salvar shaped. Flower is actinomorphic and incomplete. The sepals and petals are five (pentamerous) and free. The sepals are arranged in imbricate aestivation. The petals are valvate and connitent at the flower base forming a short tube. Stamens are ten, diadelphous, arranged in two tiers of five each. The outer tier is free, while the inner tier is united. The anthers are yellow, dithecous and dorsifixed. The pollen grains are yellow, globular and inaperturate. Female flower is quite similar to the male flower in shape, color and slightly fragrant, but is relatively larger. Sepals and petals are same as male flower. The styles and stigmas are both three and free. The stigmas are green, darker than petals and are bifid. The ovary is tricarpellary, united, one ovule in each chamber arranged in axile placentation. The floral base is villose, and contains five elliptical glands under the ovary. Anthesis started from 06.50 am and lasted up to 11.50 am. Anthers dehisced at a mean time of 1.28 h after flower opening. The stigma attained receptivity between 01.20 pm to 2.25 pm and remained so for 2-3 days. The estimated average number of pollen grains per flower was 1601 ± 70. The pollen exhibited 91.06 ± 2.42 per cent fertility. In open pollination, the percentage of fruit set was 4.95 (highest among different modes) in relation to total number of flower buds established. The flowers exhibited both entomophilous way of pollination and wind pollination. Honeybees (Apis indica, A. dorsata, and A. florae) were observed as the predominant insect pollinators. The fruit attained yellow to brown colour at 16 to 19 days after fruit set. The average maximum length (33.23 mm) and diameter (29.17 mm) were recorded in greenish yellow coloured fruit followed by yellow coloured fruit with 31.97 mm length and 28.47 mm diameter. The flower drop in inflorescence was 94.01 per cent and only 3.99 per cent of flowers set in to fruits. Hundred per cent germination was obtained for the seeds collected from yellow coloured fruits, followed by 96.67 per cent germination from seeds of brown coloured fruits. The least germination percentage (80%) was obtained from seeds of black coloured fruits. The maximum seed length (21.54 mm) and diameter (10.71 mm) were recorded in greenish yellow coloured fruits. The average moisture content and density of seed were noted as 13.39 per cent and 0.814 g/cc respectively. The crude oil extracted from the seed was 37.5 per cent. The seed contained protein - 14.58 per cent (kernel-12.26%, shell-2.32%), carbohydrate - 14.58 per cent (kernel-10.43%, shell-1.95%) and free fatty acid – 9.5 per cent (kernel-8.54, shell-0.96).